2022
DOI: 10.1155/2022/2518340
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Assessment of Oxidative Stress-Related Genes in Colorectal Cancer and New Insights into Tumor Immunity

Abstract: Oxidative stress is crucial to the biology of tumors. Oxidative stress’ potential predictive significance in colorectal cancer (CRC) has not been studied; nevertheless here, we developed a forecasting model based on oxidative stress to forecast the result of CRC survival and enhance clinical judgment. The training set was chosen from the transcriptomes of 177 CRC patients in GSE17536. For validation, 65 samples of colon cancer from GSE29621 were utilized. For the purpose of choosing prognostic genes, the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Researches have shown that OSGIN2 may be involved in the physiological processes of cancer and other diseases 13 , 14 . Chen Z et al 21 also observed high expression of OSGIN2 in colorectal cancer tissues. Our study confirmed the association of OSGIN2 with gastric cancer and suggested it as a potential marker for the diagnosis and prognosis of GC by bioinformatics analysis and experimental validation.…”
Section: Discussionmentioning
confidence: 90%
“…Researches have shown that OSGIN2 may be involved in the physiological processes of cancer and other diseases 13 , 14 . Chen Z et al 21 also observed high expression of OSGIN2 in colorectal cancer tissues. Our study confirmed the association of OSGIN2 with gastric cancer and suggested it as a potential marker for the diagnosis and prognosis of GC by bioinformatics analysis and experimental validation.…”
Section: Discussionmentioning
confidence: 90%
“… 41 AARS2 contributes to mitochondrial respiration and has been identified as a protective factor in the prognostic model of colorectal cancer. 42 Zhu et al suggested a gene signature containing AARS2 and VARS2 via involving mitochondrial respiration and proliferation in COAD. 43 VARS2 polymorphisms were found in a candidate prognostic marker for early breast cancer 44 and were associated with mitochondrial respiratory chain and oxidative phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Although CBS and CSE may contribute to the synthesis of H 2 S under physiological conditions, their substantial contributions depend on the activity levels of this enzyme expressed in different cells and tissues as well as under various cellular metabolic conditions [ 1 , 2 , 9 , 36 , 37 , 38 , 39 ]. For example, these canonical enzymes and Cars2 are known to be highly expressed in cancer tissues such as human Basal-like breast cancers and colorectal cancer tissues [ 40 , 41 ]. In the breast cancer tissues where CBS and CSE are highly expressed, CBS and CSE play important roles in sulfur metabolism and tumorigenesis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%